Diferencias en el desempeño de conciencia fonológica en niños de 5 años de dos instituciones educativas: Bocanegra - Callao - Espinoza Gallegos, Elízabeth Rosa (2010)
The research was to compare the performance in phonological awareness in two groups of children 5 years of age in educational institutions No. 111 and No. 115 of the Initial Level Bocanegra, Callao. It is a comparative descriptive study, whose sample consisted of 120 children. The selection of the sample was probabilistic, who have applied the test of metalinguistic skills Gomez, Valero, Buades and Perez (1995). To compare the differences between means were used Mann Whitney U test and found no differences in levels of phonological awareness in children of School No. 111 in front of children of School No. 115.